Postsynthetic treatment of nickel–iron layered double hydroxides for the optimum catalysis of the oxygen evolution reaction - Tyndall, Daire (2022)
D.T., S.J., J.C., and V.N. wish to thank the support of the ERC CoG, 3D2DPring (GA 681544) and PoC Powering_eTextiles (GA 861673) and SFI AMBER (12/RC/2278_P2). The authors would like to thank the Advanced Microscopy Lab and CRANN Trinity College Dublin for providing STEM-EDX measurements. This publication has emanated from research supported in part by a grant from Science Foundation Ireland under Grant number 12/RC/2278_P2. For the purpose of Open Access, the author has applied a CC BY public copyright licence to any Author Accepted Manuscript version arising from this submission. Publisher Copyright: © 2021, The Author(s).